Case report: Plasmablastic neoplasm with multinucleated giant cells—Analysis of stemness of the neoplastic multinucleated giant cells - Otsuka-Kamakura, Narumi; Sugiura, Yoshiya; Yamazaki, Toshiki; Shimizu, Naomi; Hiruta, Nobuyuki (Frontiers in Oncology, 2022)
Cancer stem cells have the capability of self-renewal and multipotency and are, therefore, associated with tumor heterogeneity, resistance to chemoradiation therapy, and metastasis. The hypothesis that multinucleated giant cells, which often emerge following chemo- and/or radiotherapy, serve as cancer stem cells has not been fully evaluated. Although a previous study demonstrated that these cells functioned as stem cells, only low levels of Yamanaka factors were expressed, contrasting with the high expression seen from their gestated first-generation mononuclear cells. Herein, we report a case of a plasmablastic neoplasm with multinucleated giant cells that were analyzed for stemness to test the above hypothesis. The patient was a male in his 80s who had a plasmablastic neoplasm that was not easily distinguishable as plasmablastic lymphoma versus plasma cell myeloma of plasmablastic type. Lymph node biopsy showed predominant mononuclear cell proliferation with admixed multinucleated giant cells. Immunohistochemistry and in situ hybridization showed that both multinucleated and mononuclear cells had the same profile: CD138(+), light chain restriction of κ>λ, cyclin D1(+), CD68(-), EBER-ISH (+). These results suggested that both cell types were neoplastic. In accordance with the previous study, the multinucleated giant cells showed low expression of Yamanaka factors, which were highly expressed in some of the mononuclear cells. Furthermore, the multinucleated giant cells showed a much lower proliferative activity (Mib1/Ki67 index) than the mononuclear cells. Based on these results, the multinucleated giant cells were compatible with cancer stem cells. This case is expected to expand the knowledge base regarding biology of cancer stem cells.